Biliary complications post liver resection for pediatric liver tumors - Kok Hoi Teh; Mohd Yusran Othman; Zakaria Zahari (BMJ Publishing Group, 2023)
Objective To review biliary complications following liver resection for liver tumors in children and their associated risk factors.Methods Retrospectively, we reviewed children who underwent liver resection for liver tumors from 2010 to 2019. Demographic data, operative details, types of complications, interventions and outcomes were studied.Results Eighty-six out of 108 liver resections were included in this study. The median age of patients was 1.8 years old, and 55% were male. The majority (95%) were malignant tumors, of which 87% were hepatoblastoma (n=71). The most common procedure performed was extended right hepatectomy (37%, n=32). Twelve (14%) patients had primary biliary complications: nine bile leakages and three biliary obstructions. Six cases of bile leakage were treated non-operatively with drainage only; however, one developed bilothorax. Three bile leakages underwent early operative intervention. Four patients underwent biliary reconstruction. Biliary complications were not significantly associated with age, sex, ethnicity or pathology of the tumor. Ten of them (83%) developed following extended hepatectomies (five right, five left), in which the left side had a higher rate of complications (63% vs 16%). None of the central hepatectomies had biliary complications. Biliary complication rates were significantly higher among those who had segmentectomy 1 (p=0.023).Conclusions Biliary complication is a significant morbidity following liver resection in children. Surgery is eventually required for complicated bile leakage and primary biliary strictures. Follow-up is mandatory since secondary biliary complications may occur after the initial resolution of bile leakage. The groups at high risk of developing biliary complications are extended left hepatectomies and segmentectomy 1.